(untitled) (Communications in Computational Physics, 2020)
The lattice Boltzmann method (LBM) for multicomponent immiscible fluids is applied to the simulations of solid-fluid mixture flows including spherical or nonspherical particles in a square pipe at Reynolds numbers of about 100. A spherical solid particle is modeled by a droplet with strong interfacial tension and large viscosity, and consequently there is no need to track the moving solid-liquid boundary explicitly. Nonspherical (discoid, flat discoid, and biconcave discoid) solid particles are made by applying artificial forces to the spherical droplet. It is found that the spherical particle moves straightly along a stable position between the wall and the center of the pipe (the Segré-Silberberg effect). On the other hand, the biconcave discoid particle moves along a periodic helical path around the center of the pipe with changing its orientation, and the radius of the helical path and the polar angle of the orientation increase as the hollow of the concave becomes large.